Stress Coping Framework As an Effort To Improve Quality of Life Patients with Chronic Obstructive Pulmonary Disease: A Literature Review - Sutrisno, Sutrisno; Rondhianto, Rondhianto (Universitas Malahayati, 2024)
ABSTRACT COPD patients usually experience a decrease in quality of life due to COPD symptoms such as coughing, shortness of breath,exacerbationAcute disease and comorbidities that occur in COPD patients cause limitations in daily activities. Stress coping is one of the factors that causes good or bad self-care behavior in COPD patients. To describe the influence, stress coping and level of selfcare in COPD patients on their quality of life. The method of this study is a literature review. Literature searches using electronic databases such as PubMed, Google Scholar and Science Direct. A literature review was carried out on international journals published in the last 5 years, available in full text. The keywords used were